Curable polysiloxane composition and sealant comprising same

By using a branched polysiloxane compound with an alkenyl group and an aryl group, a curable polysiloxane composition with a hydrogen and an aryl group, a curable polysiloxane composition with a promoter compound and an inorganic filler, the problem of insufficient transmittance and mechanical properties of the existing LED sealant is solved, and high transmittance and excellent mechanical properties are achieved.

CN119546705APending Publication Date: 2025-02-28WACKER CHEMIE AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380053273.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

LED sealants made of existing silicon materials cannot meet the demand for high transmittance, and due to the intrusion of corrosive gases or water vapor, the mechanical properties of the sealant deteriorate, resulting in a reduced effect.

Method used

A curable polysiloxane composition is provided, which comprises a branched polysiloxane compound having an alkenyl group and an aryl group, a branched polysiloxane compound having a hydrogen and an aryl group, a promoter compound and an inorganic filler to improve the transparency, transmittance and mechanical properties of the sealant.

Benefits of technology

By using the sealant made of the curable polysiloxane composition, high transmittance and excellent mechanical properties can be achieved, and the sealant can be prevented from failing due to deterioration of mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237601880000031
    Figure BDA0005237601880000031
  • Figure BDA0005237601880000032
    Figure BDA0005237601880000032
  • Figure BDA0005237601880000111
    Figure BDA0005237601880000111
Patent Text Reader

Abstract

The invention provides a curable polysiloxane composition and a sealant containing the curable polysiloxane composition. The curable polysiloxane composition includes: (A) a branched polysiloxane compound having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and including a siloxane unit represented by R 'SiO3 / 2 (wherein R' is a substituted or unsubstituted monovalent hydrocarbon group); (B) a branched polysiloxane compound having at least one Si-bonded hydrogen and at least one Si-bonded aryl group per molecule and containing a siloxane unit represented by R "SiO3 / 2 (wherein R" is a substituted or unsubstituted monovalent hydrocarbon group), (C) a compound that promotes a reaction between the alkenyl group of compound (A) and the hydrogen group of compound (B), and (D) an inorganic filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable silicone composition and a sealant comprising the same. Background Art

[0002] Light-emitting diodes (LEDs) are one of the next generation display technologies. Recently, as the size of LED devices has been reduced, a technology that can protect LED devices and achieve high light transmittance of LED devices is needed. Therefore, silicon materials have attracted much attention as sealant materials for LED devices due to their excellent thermal and light stability.

[0003] However, the sealant made of silicon material cannot satisfy the high transmittance required for smooth emission of light from each light source, and suffers from mechanical degradation due to the intrusion of corrosive gas or water vapor, thereby being peeled off. As a result, the effect of the sealant is reduced.

[0004] Therefore, there is a need to develop a silicon material that can improve the effect as a sealant for LED devices while exhibiting high transmittance without deteriorating mechanical properties. Summary of the invention

[0005] [Technical issues]

[0006] Therefore, the present invention has been made in view of the above problems, and an object of the present invention is to provide a curable polysiloxane composition having excellent transparency, high transmittance, and mechanical properties, and a sealant including the curable polysiloxane.

[0007] [Technical solution]

[0008] According to one aspect of the present invention, the above and other objects can be achieved by providing a curable polysiloxane composition comprising: (A) a polysiloxane having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising R ` SiO 3 / 2 (B) a branched polysiloxane compound having a siloxane unit represented by (A) at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprising R `` SiO 3 / 2 (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B); and (D) an inorganic filler.

[0009] In one embodiment of the present invention, compound (A) can be represented by the following average unit formula 3:

[0010] [Average unit formula 1]

[0011] (R 1 R 2 R 3 SiO 1 / 2 ) a (R 4 R 5 SiO 2 / 2 ) b (R 6 SiO 3 / 2 ) c (SiO 4 / 2 ) d

[0012] wherein R 1 , R 2 and R 3 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups, and at least one of R 1 , R 2 and R 3 is an alkenyl group, R 4 and R 5 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups and aryl groups having 6 to 12 carbon atoms, R 6 is an aryl group having 6 to 12 carbon atoms, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d < 1, and a + b + c + d = 1.

[0013] In one embodiment of the present invention, compound (B) can be represented by the following average unit formula 2:

[0014] [Average unit formula 2]

[0015] (R 7 R 8 R 9 SiO 1 / 2 ) e (R 10 SiO 3 / 2 ) f (R 11 SiO 3 / 2 ) g

[0016] wherein R 7 , R 8 and R 9 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups, and at least one of R 7 , R 8 and R 9 is hydrogen, R 10 is a substituted or unsubstituted monovalent hydrocarbon group, R 11is an aryl group having 6 to 12 carbon atoms, 0 < e < 1, 0 ≤ f < 1, 0 < g < 1, and e + f + g = 1.

[0017] In one embodiment of the present invention, the compound (C) may include at least one of the compounds represented by the following Chemical Formulas 1 and 2:

[0018] [Chemical Formula 1]

[0019]

[0020] [Chemical Formula 2]

[0021]

[0022] Wherein, in Chemical Formula 1, R 12 , R 13 and R 14 are each independently an alkenyl group having 2 to 20 carbon atoms, and in Chemical Formula 2, R 15 , R 16 , R 17 and R 18 are each independently a substituted or unsubstituted monovalent hydrocarbon group, and R 19 , R 20 , R 21 and R 22 are each independently an alkenyl group having 2 to 20 carbon atoms.

[0023] In one embodiment of the present invention, relative to 100 parts by weight of the curable polysiloxane composition, the inorganic filler (D) may be included in an amount of 0.1 part by weight to 20 parts by weight.

[0024] In one embodiment of the present invention, the inorganic filler (D) may include fumed silica.

[0025] In one embodiment of the present invention, the fumed silica may include a first fumed silica having a methanol value of less than 15 and a second fumed silica having a methanol value of greater than 40.

[0026] In one embodiment of the present invention, the curable polysiloxane composition may have a refractive index of 1.45 to 1.55 at wavelengths of 480 nm and 598 nm.

[0027] In one embodiment of the present invention, a cured product having a thickness of 1 mm made from the curable polysiloxane composition may have a light transmittance of 80% or higher.

[0028] In one embodiment of the present invention, a cured product having a thickness of 1 mm made from the curable polysiloxane composition may have a Shore D hardness of 20 to 40.

[0029] According to another aspect of the present invention, there is provided a sealant comprising a curable polysiloxane composition, the curable polysiloxane composition comprising: (A) a polysiloxane having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising R ` SiO 3 / 2 (B) a branched polysiloxane compound having at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprising a siloxane unit represented by R `` SiO 3 / 2 (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B); and (D) an inorganic filler.

[0030] [Beneficial Effects]

[0031] Since the curable polysiloxane composition according to the present invention includes an inorganic filler, processability and mechanical properties may be improved.

[0032] Furthermore, since the curable polysiloxane composition according to the present invention includes a branched polysiloxane compound having an alkenyl group and an aryl group and a branched polysiloxane compound having a hydrogen group and an aryl group, and includes a compound capable of forming a silicon-carbon bond through a hydrosilylation reaction, the adhesion and transparency of a cured product made from the curable polysiloxane composition can be improved while ensuring the mechanical properties of the cured product, and the cured product can exhibit a high refractive index, thereby having improved light transmittance. DETAILED DESCRIPTION

[0033] The structural or functional descriptions of the embodiments disclosed in this specification or application are merely for the purpose of explaining the embodiments according to the technical ideas of the present invention. The embodiments according to the technical ideas of the present invention may be implemented in various forms different from the embodiments disclosed in this specification or application, and it should not be understood that the technical ideas of the present invention are limited to the embodiments described in this specification or application.

[0034] In this specification or application, unless there is no different disclosure, when a certain component is "comprising", it means that only the component is contained, or the component may further contain another component. In addition, it should be understood that, unless otherwise specified, all numerical ranges representing physical property values, sizes, etc. of components (parts) described in this specification or application are modified by the term "about" in all cases.

[0035] In addition, the meaning of each term described in this specification or application is as follows.

[0036] Siloxane: A compound with Si-O-Si bonds.

[0037] Polysiloxane: A compound with multiple Si-O-Si bonds.

[0038] Silicone composition: A composition consisting solely of a silicone compound, or a composition containing silicone and mixed with other compounds to achieve specific properties.

[0039] Linear polysiloxane: A polysiloxane having a structure in which siloxane chains are not linked by inserting an atomic linking group into the Si atom of the polysiloxane main chain (—Si—O—Si—O—).

[0040] Branched polysiloxane: a polysiloxane containing at least one T-shaped or cross-shaped branch point.

[0041] Organopolysiloxane: A polysiloxane having a structure in which an organic group is bonded to a Si atom constituting a Si-O-Si bond.

[0042] <Curable Polysiloxane Composition>

[0043] The curable polysiloxane composition according to the present invention comprises (A) a polysiloxane having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising ` SiO 3 / 2 (B) has at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprises a branched polysiloxane compound represented by R `` SiO 3 / 2 (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B), and (D) an inorganic filler.

[0044] Component (A)

[0045] The curable polysiloxane composition according to the present invention comprises (A) a polysiloxane having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising ` SiO 3 / 2 (wherein R' is a substituted or unsubstituted monovalent hydrocarbon group) is a branched polysiloxane compound having a siloxane unit represented by

[0046] Component (A) can impart strength and increased refractive index to a cured product obtained by curing the curable polysiloxane composition. Specifically, when the curable polysiloxane composition includes component (A), thermal shock resistance of the cured product can be improved, and its refractive index can be increased, thereby improving light transmittance.

[0047] Component (A) comprises a branched polysiloxane compound having -Si-O-Si-O-(polysiloxane) as a main chain and comprising at least one T-shaped or cross-shaped branch point per molecule. Preferably, component (A) may only comprise a branched polysiloxane compound, but may not comprise a linear polysiloxane compound having a structure in which a siloxane chain is not connected by inserting an atomic linking group into the Si atom of the polysiloxane main chain (-Si-O-Si-O-). Since component (A) does not comprise a linear polysiloxane compound, the cured product made of the curable polysiloxane compound may have improved transparency and improved light transmittance due to an increased refractive index.

[0048] In component (A), the alkenyl group may be a vinyl group, an allyl group, a methallyl group, a butenyl group, a pentenyl group or a hexenyl group. Preferably, the alkenyl group may be a vinyl group.

[0049] In component (A), aryl can be phenyl, naphthyl, anthracenyl, phenanthrenyl, indenyl, benzophenyl, fluorenyl, xanthenyl, anthronyl, aryloxyaryl, o-phenoxyphenyl, p-phenoxyphenyl, alkylaryl, o-tolyl, m-tolyl, p-tolyl, xylyl, ethylphenyl, aralkyl, benzyl, α-phenethyl or β-phenethyl. Preferably, aryl can be phenyl.

[0050] In component (A), in addition to alkenyl and aryl, the Si-bonded organic group may be a substituted or unsubstituted monovalent hydrocarbon group, specifically a methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl or halogenated alkyl group. Preferably, the Si-bonded organic group may be a methyl group.

[0051] In component (A), R ` SiO 3 / 2 The siloxane unit represented may refer to a branched polysiloxane compound with a T-shaped or cross-shaped branch point. R' is a substituted or unsubstituted monovalent hydrocarbon group. The substituent of the monovalent hydrocarbon group may be an alkyl, alkenyl, aryl, aralkyl or halogenated alkyl group.

[0052] Component (A) can be represented by the following average unit formula 3:

[0053] [Average unit formula 1]

[0054] (R 1 R 2 R 3SiO 1 / 2 ) a (R 4 R 5 SiO 2 / 2 ) b (R 6 SiO 3 / 2 ) c (SiO 4 / 2 ) d

[0055] In the average unit 1, R 1 , R 2 and R 3 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups, and at least one of R 1 , R 2 and R 3 is an alkenyl, R 4 and R 5 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups and aryl groups having 6 to 12 carbon atoms, R 6 is an aryl group having 6 to 12 carbon atoms, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d < 1, and a + b + c + d = 1.

[0056] The substituent of the monovalent hydrocarbon group can be an alkyl group, an alkenyl group, an aryl group, an aralkyl group or a haloalkyl group.

[0057] The alkenyl group can be a vinyl group, an allyl group, a methallyl group, a butenyl group, a pentenyl group or a hexenyl group.

[0058] The aryl group having 6 to 12 carbon atoms can be a phenyl group or a naphthyl group.

[0059] a can be 0 < a < 1, 0 < a < 0.8, 0 < a < 0.5, 0 < a < 0.3, or 0 < a < 0.2.

[0060] b can be 0 < b < 1, 0.1 < b < 1, 0.1 < b < 0.9, 0.2 < b < 0.8, or 0.3 < b < 0.7.

[0061] c can be 0 < c < 1, 0 < c < 0.8, 0 < c < 0.5, 0.1 < c < 0.5, or 0.2 < c < 0.5.

[0062] d can be 0 ≤ d < 1, 0 ≤ d < 0.5, 0 ≤ d < 0.3, 0 ≤ d < 0.2, or 0 ≤ d < 0.1.

[0063] Based on R 1 , R 2 , R 3 , R 4 , R 5 and R6 The total amount of the alkenyl group can be 0.1 mol % to 35 mol %, 1 mol % to 35 mol %, 3 mol % to 35 mol %, 3 mol % to 30 mol %, or 5 mol % to 35 mol %. Within these ranges, the curability and reactivity of the curable polysiloxane composition can be further improved.

[0064] Based on R 1 , R 2 , R 3 , R 4 , R 5 and R 6 The total amount of the aryl group can be 10 mol % to 90 mol %, 20 mol % to 90 mol %, 30 mol % to 90 mol %, 30 mol % to 80 mol %, or 40 mol % to 70 mol %. Within these ranges, phenomena such as light refraction, reflection and scattering of a cured product made from the curable polysiloxane composition can be reduced, thereby further improving its transparency and transmittance.

[0065] Component (A) may be present in a liquid or solid state at 25°C.

[0066] Component (A) may be included in an amount of 20 to 90 wt %, 30 to 90 wt %, 35 to 90 wt %, 40 to 90 wt %, or 45 to 60 wt %, based on the total weight of the curable polysiloxane composition.

[0067] Component (B)

[0068] The curable polysiloxane composition according to the present invention comprises (B) a polysiloxane having at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprising `` SiO 3 / 2 A branched polysiloxane compound having a siloxane unit represented by (wherein R" is a substituted or unsubstituted monovalent hydrocarbon group).

[0069] Component (B) may be used as a curing agent for the curable polysiloxane composition. Specifically, when the curable polysiloxane composition includes component (B), a curing reaction with component (A) by hydrosilylation may be efficiently performed.

[0070] Component (B) has -Si-O-Si-O-(polysiloxane) as the main chain, and contains a branched polysiloxane compound containing at least one T-shaped or cross-shaped branch point per molecule. Preferably, component (B) may contain only branched polysiloxane compounds, but may not contain a linear polysiloxane compound having a structure in which the siloxane chain is not connected by inserting an atomic linking group into the Si atom of the polysiloxane main chain (-Si-O-Si-O-). Since component (B) does not contain a linear polysiloxane compound, the cured product made from the curable polysiloxane compound may have improved mechanical properties and transparency.

[0071] In component (B), aryl can be phenyl, naphthyl, anthracenyl, phenanthrenyl, indenyl, benzophenyl, fluorenyl, xanthenyl, anthranyl, aryloxyaryl, o-phenoxyphenyl, p-phenoxyphenyl, alkylaryl, o-tolyl, m-tolyl, p-tolyl, xylyl, ethylphenyl, aralkyl, benzyl, α-phenethyl or β-phenethyl. Preferably, aryl can be phenyl.

[0072] In component (B), in addition to hydrogen and aryl, the Si-bonded organic group may be a substituted or unsubstituted monovalent hydrocarbon group, and specifically may be a methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl or halogenated alkyl group. Preferably, the Si-bonded organic group may be a methyl group.

[0073] In component (B), R `` SiO 3 / 2 The siloxane unit represented may refer to a branched polysiloxane compound with a T-shaped or cross-shaped branch point. R' is a substituted or unsubstituted monovalent hydrocarbon group. The substituent of the monovalent hydrocarbon group may be an alkyl, alkenyl, aryl, aralkyl or halogenated alkyl group.

[0074] Component (B) can be represented by the following average unit formula 2:

[0075] [Average unit formula 2]

[0076] (R 7 R 8 R 9 SiO 1 / 2 ) e (R 10 SiO 3 / 2 ) f (R 11 SiO 3 / 2 ) g

[0077] In the average unit formula 2, R 7 , R 8 and R 9Each independently selected from substituted or unsubstituted monovalent hydrocarbon groups, R 7 、R 8 and R 9 at least one of which is hydrogen, R 10 is a substituted or unsubstituted monovalent hydrocarbon group, R 11 is an aryl group having 6 to 12 carbon atoms, 0 < e < 1, 0 ≤ f < 1, 0 < g < 1, and e + f + g = 1.

[0078] The substituent of the monovalent hydrocarbon group may be an alkyl group, an alkenyl group, an aryl group, an aralkyl group, or a haloalkyl group.

[0079] The aryl group having 6 to 12 carbon atoms may be a phenyl group or a naphthyl group.

[0080] e may be 0 < e < 1, 0 < e < 0.8, 0.1 < e < 0.8, 0.2 < e < 0.7, or 0.2 < e < 0.6.

[0081] f may be 0 ≤ f < 1, 0 ≤ f < 0.8, 0 ≤ f < 0.7, 0 ≤ f < 0.6, or 0 ≤ f < 0.5.

[0082] g may be 0 < g < 1, 0 < g < 0.9, 0.1 < g < 0.9, 0.1 < g < 0.8, or 0.2 < g < 0.8.

[0083] Based on the total amount of R 7 、R 8 、R 9 、R 10 and R 11 , the hydrogen content may be 0.1 mol% to 40 mol%, 1 mol% to 40 mol%, 3 mol% to 40 mol%, 3 mol% to 40 mol%, or 5 mol% to 40 mol%. Within these ranges, the curing reaction with component (A) by hydrosilylation can proceed more effectively.

[0084] Based on the total amount of R 7 、R 8 、R 9 、R 10 and R 11 , the aryl content may be 10 mol% to 90 mol%, 20 mol% to 90 mol%, 30 mol% to 90 mol%, 30 mol% to 80 mol%, or 40 mol% to 70 mol%. Within these ranges, phenomena such as light refraction, reflection, and scattering of the cured product made from the curable polysiloxane composition can be reduced, thereby further improving its transparency and transmittance.

[0085] Component (B) may be included in an amount of 10 to 80 wt%, 10 to 70 wt%, 10 to 60 wt%, 10 to 50 wt%, or 20 to 50 wt%, based on the total weight of the curable polysiloxane composition.

[0086] The molar ratio of Si-bonded hydrogen in component (B) to Si-bonded alkenyl in component (A) may be 0.7 to 1.0. Within this range, the content of silicon hydride residues may be reduced and the adhesion of a cured product made from the curable polysiloxane composition may be improved.

[0087] Component (C)

[0088] The curable polysiloxane composition according to the present invention comprises (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B).

[0089] Component (C) can increase the hardness of a cured product made from a curable polysiloxane composition without changing the content of the branched polysiloxane compound in components (A) and (B). In addition, component (C) can increase the refractive index of a cured product made from a curable polysiloxane composition without changing the content of the branched polysiloxane compound in components (A) and (B).

[0090] Component (C) may be combined with a catalyst that promotes the reaction (hydrosilylation reaction) between the alkenyl group of compound (A) and hydrogen of compound (B) to form a complex compound.

[0091] The catalyst may include a platinum catalyst, a rhodium catalyst, or a palladium catalyst.

[0092] The complex compound may be a platinum / alkenylsiloxane complex compound, a platinum / olefin complex compound or a platinum / carbonyl complex compound.

[0093] Component (C) may include at least one of the compounds represented by the following Chemical Formulas 1 and 2:

[0094] [Chemical formula 1]

[0095]

[0096] [Chemical formula 2]

[0097]

[0098] In Chemical Formula 1, R 12 , R 13 and R 14 are each independently an alkenyl group having 2 to 20 carbon atoms. 15 , R16 , R 17 and R 18 are each independently a substituted or unsubstituted monovalent hydrocarbon group, and R 19 , R 20 , R 21 and R 22 Each is independently an alkenyl group having 2 to 20 carbon atoms.

[0099] The compound represented by Chemical Formula 1 may be a compound represented by the following Chemical Formula 1-1:

[0100] [Chemical formula 1-1]

[0101]

[0102] The compound represented by Chemical Formula 2 may be a compound represented by the following Chemical Formula 2-1:

[0103] [Chemical formula 2-1]

[0104]

[0105] Component (C) may be included in an amount of 1 to 30 wt%, 1 to 25 wt%, 1 to 20 wt%, 1 to 18 wt%, or 1 to 15 wt%, based on the total weight of the curable polysiloxane composition.

[0106] The catalyst may be included in an amount of 0.1 ppm to 10 ppm, 0.1 ppm to 8 ppm, 0.1 ppm to 7 ppm, 1 ppm to 7 ppm, or 1 ppm to 5 ppm based on the total weight of the curable polysiloxane composition.

[0107] Component (D)

[0108] The curable polysiloxane composition according to the present invention comprises (D) an inorganic filler.

[0109] Component (D) can improve the processability and mechanical properties of a cured product made from the curable polysiloxane composition.

[0110] The inorganic filler may include inorganic oxide particles such as silicon dioxide, barium titanate, titanium oxide, zirconium oxide, niobium oxide, aluminum oxide, cerium oxide, or yttrium oxide, nitride particles such as silicon nitride, boron nitride, silicon carbide, or aluminum nitride, carbon compound particles, or diamond particles.

[0111] The inorganic filler may include fumed silica.

[0112] Fumed silica is a commercial product or can be prepared by standard chemical methods.Fumed silica can be prepared by hydrolysis or oxidation of volatile chlorosilanes in a hydrogen / oxygen flame.

[0113] The fumed silica may include a first fumed silica having a methanol value less than 15 and a second fumed silica having a methanol value greater than 40. Preferably, the methanol value of the first fumed silica may be 0, and the methanol value of the second fumed silica may be greater than 50.

[0114] The methanol value may refer to the percentage (weight %) of methanol that sinks into the liquid in a water / methanol mixture under the conditions of 25° C. and 1013 hPa in a state where about 50% of the fumed silica is wet.

[0115] The methanol value can be determined by the following method. An equal volume of each fumed silica is added to a water / methanol mixture at 25°C and 1013 hPa. Next, after mixing for 5 minutes, the mixture is aged for 10 minutes. Next, the amount of silica precipitated in the mixture is determined. If the fumed silica does not precipitate in the mixture when observed with the naked eye, the experiment is repeated.

[0116] The first fumed silica may refer to relatively hydrophilic silica, and the second fumed silica may refer to relatively hydrophobic silica. Since component (D) includes both hydrophilic silica and hydrophobic silica, the hardness of the curable polysiloxane composition can be increased, thereby improving mechanical properties, thermal shock resistance, formability, and processability.

[0117] The content of component (D) may be 0.1 to 20 parts by weight, 1 to 20 parts by weight, 1 to 18 parts by weight, or 3 to 10 parts by weight relative to 100 parts by weight of the curable polysiloxane composition. Within these ranges, mechanical properties may be improved without reducing transparency and transmittance.

[0118] Other additives

[0119] The curable polysiloxane composition according to the present invention may further contain a curing inhibitor, phosphorus, polymethacrylate resin fine powder, a heat stabilizer, a dye, a pigment, a flame retardant, a solvent, and the like, as required.

[0120] In addition, the curable polysiloxane composition may further include a tackifier to increase adhesion.

[0121] Adhesion promoters may include epoxy silanes such as glycidoxypropyl trimethoxysilane, glycidoxypropyl methyl dimethoxysilane, glycidoxypropyl triethoxysilane or glycidoxypropyl methyl diethoxysilane, 2-(3-triethoxysilylpropyl) maleic anhydride, N-(3-trimethoxysilylpropyl) urea, N-(3-triethoxysilylpropyl) urea, N-(trimethoxysilylmethyl) urea, N-(methyldimethoxysilylmethyl) urea, O-(methylcarbamoylmethyl) methyl dimethoxysilane, O- (Methylcarbamoylmethyl)trimethoxysilane, O-(ethylcarbamoylmethyl)methyldiethoxysilane, O-(ethylcarbamoylmethyl)triethoxysilane, 3-methacryloxypropyltrimethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxymethylmethyldimethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, acryloxymethyltrimethoxysilane, or acryloxymethylmethyldimethoxysilane.

[0122] The tackifier may be included in an amount of 0.1 wt % to 10 wt %, 0.1 wt % to 5 wt %, 0.1 wt % to 3 wt %, or 0.1 wt % to 2 wt %, based on the total weight of the curable polysiloxane composition.

[0123] Physical Properties of Curable Polysiloxane Compositions

[0124] The curable polysiloxane composition can have a refractive index of 1.45 to 1.55 at a wavelength of 480nm and a wavelength of 598nm. The refractive index can be measured using an Abbe refractometer at a D line (480nm, 589nm) wavelength of a cured product made from a curable polysiloxane composition or a precured composition. Within this range, the transparency and mechanical properties of the cured product made from the curable polysiloxane composition can be improved.

[0125] The cured product having a thickness of 1 mm made from the curable polysiloxane composition can have a light transmittance of 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, or 90% or more. Within these ranges, when the cured product made from the curable polysiloxane composition is used as an LED sealant, light can be smoothly emitted from each light source.

[0126] The cured product having a thickness of 1 mm made from the curable polysiloxane composition may have a Shore D hardness of 20 to 40, 22 to 40, 24 to 40, 26 to 40, or 28 to 40. After the curable polysiloxane composition is injected into a Teflon-coated mold having a width of 4 cm×5 cm length×6 mm thickness, cured at 190° C. for 10 minutes, and then cooled at room temperature to prepare a cured product, the Shore D hardness of the cured product may be measured with a D hardness tester. Within these ranges, the mechanical properties and thermal shock resistance of the cured product made from the curable polysiloxane composition may be improved.

[0127] <Sealant>

[0128] The sealant according to the present invention comprises a curable polysiloxane composition comprising (A) a polysiloxane having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising R ` SiO 3 / 2 (B) has at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprises a branched polysiloxane compound represented by R `` SiO 3 / 2 (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B), and (D) an inorganic filler.

[0129] Components (A) to (D) of the curable polysiloxane composition may be the same as components (A) to (D) described above.

[0130] The sealant may have a film shape or a sheet shape obtained by curing the curable polysiloxane composition.

[0131] The sealant can be used as a sealant for displays or semiconductors.

[0132] The encapsulant may be provided in the form of encapsulating, covering or adhering a display optical device or a semiconductor optical device. The optical device may be a light emitting diode (LED).

[0133] Since the light emitting diode (LED) emits light from the upper side, lower side, left side and right side of the optical element, it is not desirable for the sealant to absorb light, and the sealant should exhibit high transmittance. In addition, since the light emitting diode (LED) requires stability against high temperature and mechanical impact, the thermal stability and mechanical properties of the sealant are required. Therefore, since the curable polysiloxane composition according to the present invention has high transparency, transmittance and mechanical properties as described above, when a cured product made of the curable polysiloxane composition is used as a sealant, excellent transmittance, thermal stability and mechanical properties can be achieved.

[0134] Hereinafter, the present invention is described in more detail based on Examples and Comparative Examples. However, the following Examples and Comparative Examples are merely examples for explaining the present invention in more detail, and the present invention is not limited by the following Examples or Comparative Examples.

[0135] Example

[0136] The curable silicone composition of each of Examples 1 to 6 and Comparative Examples 1 to 5 was prepared using the following components and compositions shown in Table 1.

[0137] Synthesis of component (a-1): 1 kg of a mixed solvent was charged into a three-necked flask, the mixed solvent being obtained by mixing water and toluene in a weight ratio of 1:9. A monomer mixture in which the molar ratio of vinyldimethylchlorosilane:dimethyldichlorosilane:phenyltrichlorosilane was 1:6:3 was added to the flask while maintaining the temperature at 23°C. Next, a polycondensation reaction was carried out while refluxing at 60°C for 3 hours. Next, the flask was cooled to room temperature, and then the water layer (H2O) was removed to prepare a solution. The solution was dissolved in toluene. Next, the solution was washed with water to remove chlorine as a by-product. Next, the neutral solution was distilled under reduced pressure to remove toluene, and a branched polysiloxane compound represented by the following average unit formula was obtained:

[0138] - Average unit formula of component (a-1): (Me2ViSiO 1 / 2 ) 0.11 (diMeSiO 2 / 2 ) 0.63 (PhSiO 3 / 2 ) 0.26

[0139] Synthesis of component (a-2): 1 kg of a mixed solvent was charged into a three-necked flask, the mixed solvent being obtained by mixing water and toluene in a weight ratio of 1:9. A monomer mixture in which the molar ratio of vinyldimethylchlorosilane:methylphenyldichlorosilane:phenyltrichlorosilane was 2:3:5 was added to the flask while maintaining the temperature at 23°C. Next, a polycondensation reaction was carried out while refluxing at 60°C for 3 hours. Next, the flask was cooled to room temperature, and then the water layer (H2O) was removed to prepare a solution. The solution was dissolved in toluene. Next, the solution was washed with water to remove chlorine as a by-product. Next, the neutral solution was distilled under reduced pressure to remove toluene, and a branched polysiloxane compound represented by the following average unit formula was obtained:

[0140] - Average unit formula of component (a-2): (Me2ViSiO 1 / 2 ) 0.23 (MePhSiO 2 / 2 ) 0.32 (PhSiO 3 / 2 ) 0.45

[0141] Synthesis of component (a-3): 1 kg of a mixed solvent was charged into a three-necked flask, the mixed solvent being obtained by mixing water and toluene in a weight ratio of 1:9. A monomer mixture in which the molar ratio of vinyldimethylchlorosilane:methylphenyldichlorosilane:phenyltrichlorosilane was 1:2:7 was added to the flask while maintaining the temperature at 23°C. Next, a polycondensation reaction was carried out while refluxing at 90°C for 3 hours. Next, the flask was cooled to room temperature, and then the water layer (H2O) was removed to prepare a solution. The solution was dissolved in toluene. Next, the solution was washed with water to remove chlorine as a by-product. Next, the neutral solution was distilled under reduced pressure to remove toluene, and a branched polysiloxane compound represented by the following average unit formula was obtained:

[0142] - Average unit formula of component (a-3): (Me2ViSiO 1 / 2 ) 0.11 (MePhSiO 2 / 2 ) 0.21 (PhSiO 3 / 2 ) 0.68

[0143] Component (a-4): a linear polysiloxane compound represented by the following average unit formula

[0144] - Average unit formula of component (a-4): ViMe2SiO(Me2SiO) 20 SiMe2Vi

[0145] Synthesis of component (b-1): 500 g of a mixed solvent was charged into a three-necked flask, the mixed solvent being obtained by mixing water and toluene in a weight ratio of 1:9. A monomer mixture in which the molar ratio of dimethylchlorosilane:phenyltrichlorosilane:methyltrichlorosilane was 3.5:2.5:4 was added to the flask while maintaining the temperature at 23°C. Next, a polycondensation reaction was carried out while refluxing at 30°C for 3 hours. Next, the flask was cooled to room temperature, and then the water layer (H2O) was removed to prepare a solution. The solution was dissolved in toluene. Next, the solution was washed with water to remove chlorine as a by-product. Next, the neutral solution was distilled under reduced pressure to remove toluene, and a branched polysiloxane compound represented by the following average unit formula was obtained:

[0146] - Average unit formula of component (b-1): (HMe2SiO 1 / 2 ) 0.35 (MeSiO 3 / 2 ) 0.40 (PhSiO 3 / 2 ) 0.25

[0147] Synthesis of component (b-2): 500 g of a mixed solvent was charged into a three-necked flask, the mixed solvent being obtained by mixing water and toluene in a weight ratio of 1:9. A monomer mixture in which the molar ratio of dimethylchlorosilane:phenyltrichlorosilane was 4.5:5.5 was added to the flask while maintaining the temperature at 23°C. Next, a polycondensation reaction was carried out while refluxing at 30°C for 1 hour. Next, the flask was cooled to room temperature, and then the water layer (H2O) was removed to prepare a solution. The solution was dissolved in toluene. Next, the solution was washed with water to remove chlorine as a by-product. Next, the neutral solution was distilled under reduced pressure to remove toluene, and a branched polysiloxane compound represented by the following average unit formula was obtained:

[0148] - Average unit formula of component (b-2): (HMe2SiO 1 / 2 ) 0.44 (PhSiO 3 / 2 ) 0.56

[0149] Synthesis of component (b-3): 500 g of a mixed solvent was charged into a three-necked flask, the mixed solvent being obtained by mixing water and toluene in a weight ratio of 1:9. A monomer mixture in which the molar ratio of dimethylchlorosilane:phenyltrichlorosilane:methyltrichlorosilane was 2:1:7 was added to the flask while maintaining the temperature at 23°C. Next, a polycondensation reaction was carried out while refluxing at 30°C for 3 hours. Next, the flask was cooled to room temperature, and then the water layer (H2O) was removed to prepare a solution. The solution was dissolved in toluene. Next, the solution was washed with water to remove chlorine as a by-product. Next, the neutral solution was distilled under reduced pressure to remove toluene, and a branched polysiloxane compound represented by the following average unit formula was obtained:

[0150] - Average unit formula of component (b-3): (HMe2SiO 1 / 2 ) 0.21 (MeSiO 3 / 2 ) 0.71 (PhSiO 3 / 2 ) 0.08

[0151] Component (b-4): a linear polysiloxane compound represented by the following average unit formula

[0152] - Average unit formula of component (b-4): HMe2SiO(Ph2SiO)SiMe2H

[0153] Component (c-1): a compound represented by the following chemical formula 1-1:

[0154] [Chemical formula 1-1]

[0155]

[0156] Component (c-2): a compound represented by the following chemical formula 2-1:

[0157] [Chemical formula 2-1]

[0158]

[0159] Component (d-1): fumed silica (methanol value: 0, specific surface area: 150m 2 / g)

[0160] Component (d-2): fumed silica (methanol value: 75, specific surface area: 150m 2 / g)

[0161] Component (e): Tackifier (GF 80, manufactured by GENIOSIL)

[0162] Component (f): Catalyst (Pt-CS2.0, manufactured by Unicore)

[0163] Experimental Examples

[0164] Experimental Example 1 - Viscosity Measurement

[0165] For the compositions of Examples 1 to 6 and Comparative Examples 1 to 5 before curing, the viscosity was measured at a shear rate of 10 / s at 25° C. according to ISO 3219, and the results are shown in Table 1 below.

[0166] Experimental Example 2 - Refractive Index Measurement

[0167] For the compositions of Examples 1 to 6 and Comparative Examples 1 to 5 before curing, the refractive index was measured at a wavelength of D line (480 nm, 589 nm) using an Abbe refractometer. The results are shown in Table 1 below.

[0168] Experimental Example 3-Confirmation of Aggregated Particles

[0169] Each of the compositions of Examples 1 to 6 and Comparative Examples 1 to 5 before curing was placed on a slide glass and then compressed, and the generation of aggregated particles was visually observed through a microscope. The results are shown in Table 1 below.

[0170] Experimental Example 4-Dome Lens Shape Confirmation

[0171] Each of the compositions of Examples 1 to 6 and Comparative Examples 1 to 5 before curing was dispensed on a PCB substrate in the shape of a dome lens having a size of about 2.5 mm using a jet dispenser. The side surface of the dome lens of each of Examples 1 to 6 and Comparative Examples 1 to 5 was observed by a microscope and evaluated according to the following criteria. The results are shown in Table 1 below.

[0172] -◎: With a height of 0.5mm to 1mm, the dome shape is not distorted or offset

[0173] -○: With a height of 0.5mm to 1mm, the dome shape is distorted or offset

[0174] -X: has a height less than 0.5mm, the dome shape is distorted or offset

[0175] Experimental Example 5 - Hardness Measurement

[0176] The composition of each of Examples 1 to 6 and Comparative Examples 1 to 5 was placed in a Teflon-coated mold having a width of 4 cm×5 cm length×6 mm thickness, cured at 190° C. for 10 minutes, and then cooled at room temperature. Next, the hardness of the cured product was measured using a Shore D hardness tester, and the results are shown in Table 1 below.

[0177] Experimental Example 6-Transparency Evaluation

[0178] The transparency of the cured product produced in Experimental Example 5 was evaluated according to the following criteria, and the results are shown in Table 1 below.

[0179] -◎: When observed with the naked eye, the entire cured product is transparent

[0180] -○: A portion of the cured material is opaque when viewed with the naked eye

[0181] -X: The entire cured product is opaque when observed with the naked eye Experimental Example 7 - Evaluation of surface smoothness

[0182] The surface of the cured product produced in Experimental Example 5 was visually observed using a microscope and then evaluated according to the following criteria. The results are shown in Table 1 below.

[0183] -○: No wrinkles were observed on the surface of the cured product

[0184] -X: Wrinkles are observed on the surface of the cured product

[0185] Experimental Example 8 - Transmittance Measurement

[0186] The composition of each of Examples 1 to 6 and Comparative Examples 1 to 5 was placed in a Teflon-coated mold having a width of 4 cm×5 cm length×1 mm thickness, cured at 190° C. for 10 minutes, and then cooled at room temperature. Next, the transmittance (based on a wavelength of 450 nm) of each cured product was measured using a Specord 200Plus UV-Vis spectrometer, and the results are shown in Table 1 below.

[0187] Experimental Example 9-Heat Shock Evaluation

[0188] Thermal shock evaluation

[0189] 100 drops of the composition of Example 1 were dispensed on a PCB substrate in the form of a dome lens of about 2.5 mm size using a jet dispenser, and then thermally cured at 190° C. for 10 minutes, followed by cooling at room temperature to prepare 100 dome lens shapes. In addition, in the same manner as in Example 1, 100 dome lenses were prepared from the composition of each of Examples 2 to 6 and Comparative Examples 1 to 5.

[0190] The dome lens was exposed to each of the low temperature (-45°C) chamber and the high temperature (125°C) chamber for 15 minutes as one cycle. After 200 cycles, it was confirmed whether the dome lens was peeled off on the PCB substrate. The thermal shock was evaluated according to the following criteria, and the results are shown in Table 1 below.

[0191] -◎: No dome lens peeled off from the substrate

[0192] -○: No dome lens peeled off from the substrate, but one dome lens was lifted

[0193] -X: There is a dome lens peeling off from the substrate

[0194] Experimental Example 10-Adhesion Measurement

[0195] Each of the compositions of Examples 1 to 6 and Comparative Examples 1 to 5 was dispensed on a PCB substrate in the form of a dome lens of about 2.5 mm size using a jet dispenser, and then thermally cured at 190° C. for 10 minutes. Next, the adhesion between the dome lens and the PCB substrate was measured under the following conditions using a wafer shear strength tester.

[0196] -Test speed: 700μm

[0197] - Shear height: 30μm

[0198] -Test load: 400g

[0199] -Maximum test load: 5,000g

[0200] [Table 1]

[0201]

[0202]

[0203] Referring to Table 1, it can be confirmed that Examples 1 to 6 exhibit excellent transparency, light transmittance, adhesion, and mechanical properties.

[0204] It can be confirmed that Comparative Examples 1 and 2 exhibit reduced transparency, particularly significantly reduced light transmittance, compared to Examples 1 to 6. Furthermore, it can be confirmed that Comparative Example 3 exhibits significantly reduced transparency and light transmittance, compared to Examples 1 to 6.

[0205] It can be confirmed that, compared with Examples 1 to 6, Comparative Example 4 exhibited decreased transparency, thermal shock resistance, and adhesion, and uneven surface properties.

[0206] It can be confirmed that Comparative Example 5 did not show reduced transparency and light transmittance, but showed significantly reduced mechanical properties and thermal shock resistance, compared with Examples 1 to 6.

[0207] In summary, it was confirmed that when the cured products made of the compositions of Comparative Examples 1 to 5 were used as sealants for light emitting diodes (LEDs), the durability of the sealant may be reduced or the sealant may absorb a large amount of light, thereby possibly reducing product reliability.

Claims

1. A curable polysiloxane composition comprising: (A) having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising ` SiO 3 / 2 (wherein R' is a substituted or unsubstituted monovalent hydrocarbon group) represented by a branched polysiloxane compound of a siloxane unit; (B) having at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprising `` SiO 3 / 2 (wherein R`` is a substituted or unsubstituted monovalent hydrocarbon group) represented by a branched polysiloxane compound; (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B); and (D) Inorganic filler.

2. The curable polysiloxane composition according to claim 1, wherein the compound (A) is represented by the following average unit formula 3: [Average unit formula 1] (R 1 R 2 R 3 SiO 1 / 2 ) a (R 4 R 5 SiO 2 / 2 ) b (R 6 SiO 3 / 2 ) c (SiO 4 / 2 ) d wherein R 1 , R 2 and R 3 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups, at least one of R 1 , R 2 and R 3 is an alkenyl group, R 4 and R 5 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups and aryl groups having 6 to 12 carbon atoms, R 6 is an aryl group having 6 to 12 carbon atoms, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d < 1, and a + b + c + d = 1.

3. The curable polysiloxane composition according to claim 1, wherein the compound (B) is represented by the following average unit formula 2: [Average unit formula 2] (R 7 R 8 R 9 SiO 1 / 2 ) e (R 10 SiO 3 / 2 ) f (R 11 SiO 3 / 2 ) g wherein R 7 , R 8 and R 9 are each independently selected from substituted or unsubstituted monovalent hydrocarbon groups, at least one of R 7 , R 8 and R 9 is hydrogen, R 10 is a substituted or unsubstituted monovalent hydrocarbon group, R 11 is an aryl group having 6 to 12 carbon atoms, 0 < e < 1, 0 ≤ f < 1, 0 < g < 1, and e + f + g = 1.

4. The curable polysiloxane composition according to claim 1, wherein the compound (C) comprises at least one of the compounds represented by the following Chemical Formulas 1 and 2: [Chemical formula 1] [Chemical formula 2] in, In Chemical Formula 1, R 12 , R 13 and R 14 are each independently an alkenyl group having 2 to 20 carbon atoms, and In chemical formula 2, R 15 , R 16 , R 17 and R 18 are each independently a substituted or unsubstituted monovalent hydrocarbon group, and R 19 , R 20 , R 21 and R 22 Each is independently an alkenyl group having 2 to 20 carbon atoms. 5 . The curable polysiloxane composition according to claim 1 , wherein the inorganic filler (D) is included in an amount of 0.1 parts by weight to 20 parts by weight relative to 100 parts by weight of the curable polysiloxane composition. 6 . The curable polysiloxane composition according to claim 1 , wherein the inorganic filler (D) comprises fumed silica. 7 . The curable polysiloxane composition according to claim 6 , wherein the fumed silica comprises a first fumed silica having a methanol value of less than 15 and a second fumed silica having a methanol value of greater than 40. 8 . The curable polysiloxane composition according to claim 1 , wherein the curable polysiloxane composition has a refractive index of 1.45 to 1.55 at a wavelength of 480 nm and a wavelength of 598 nm. 9 . The curable polysiloxane composition according to claim 1 , wherein a cured product made from the curable polysiloxane composition having a thickness of 1 mm has a light transmittance of 80% or more. 10 . The curable polysiloxane composition according to claim 1 , wherein a cured product made from the curable polysiloxane composition having a thickness of 1 mm has a Shore D hardness of 20 to 40.

11. A sealant comprising a curable polysiloxane composition, the curable polysiloxane composition comprising: (A) having at least one Si-bonded alkenyl group and at least one Si-bonded aryl group per molecule and comprising ` SiO 3 / 2 (wherein R' is a substituted or unsubstituted monovalent hydrocarbon group) represented by a branched polysiloxane compound of a siloxane unit; (B) having at least one Si-bonded hydrogen and at least one Si-bonded aromatic group per molecule and comprising `` SiO 3 / 2 (wherein R`` is a substituted or unsubstituted monovalent hydrocarbon group) represented by a branched polysiloxane compound; (C) a compound that promotes the reaction between the alkenyl group of the compound (A) and the hydrogen of the compound (B); and (D) Inorganic filler.